2009
DOI: 10.1016/j.jvs.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thoracoabdominal aneurysm repair on quality of life

Abstract: Quality of life for patients undergoing TAAA repair who survive to attend follow-up in an ambulatory setting can be measured using reliable and valid instruments. Preoperatively, QOL is poor compared with healthy controls. After surgery, at 6- and 12-month follow-up, QOL seems to return to the preoperative levels. Further research is necessary to address responsiveness and sensitivity of QOL measuring tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…22,23 In general, patients treated by open surgical repair for TAAAs have poorer health-related QOL status preoperatively than a healthy control population. 24,25 In this study, we identified that physical domains of patients with TAAAs were lower than those of patients with PAAs. The exact reason for this difference is unclear, given that age and most of the cardiovascular risk factors were similar in both groups.…”
Section: Discussionmentioning
confidence: 73%
“…22,23 In general, patients treated by open surgical repair for TAAAs have poorer health-related QOL status preoperatively than a healthy control population. 24,25 In this study, we identified that physical domains of patients with TAAAs were lower than those of patients with PAAs. The exact reason for this difference is unclear, given that age and most of the cardiovascular risk factors were similar in both groups.…”
Section: Discussionmentioning
confidence: 73%
“…Endovascular repair is appealing, because many believe that extensive aortic operations may adversely affect long-term quality of life (QoL) [9,10]. Few studies, however, have evaluated QoL after extensive thoracoabdominal aortic operations [9][10][11], and no study has specifically evaluated this in patients with MFS. MFS, a systemic connective tissue disorder, has many cardiovascular and noncardiovascular symptoms that affect QoL [12].…”
mentioning
confidence: 99%
“…This tool serves as a convenient and fairly universal way to assess any treatment method with the maximum accuracy of the estimated values. 2932 Using 5-point Likert scale instrument, Thors et al, reported high satisfaction in 100% of patients after endovascular treatment for PCS. 33…”
Section: Discussionmentioning
confidence: 99%
“…This tool serves as a convenient and fairly universal way to assess any treatment method with the maximum accuracy of the estimated values. [29][30][31][32] Using 5-point Likert scale instrument, Thors et al, reported high satisfaction in 100% of patients after endovascular treatment for PCS. 33 In the present study, the authors focused the attention of patients only on assessing the outcomes of endovascular embolization and endoscopic resection of the gonadal veins for treating PeVD.…”
Section: Patients' Satisfaction With Treatment At Month 6 After Inter...mentioning
confidence: 99%